2003
DOI: 10.1562/0031-8655(2003)077<0638:eopinc>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of p-THPP into Nanoparticles: Cellular Uptake, Subcellular Localization and Effect of Serum on Photodynamic Activity¶

Abstract: The cellular uptake, localization and efflux of meso-tetra-(4-hydroxyphenyl)porphyrin (p-THPP)-loaded nanoparticles have been studied in EMT-6 tumor cells. The effect of blood serum on photocytotoxicity has also been evaluated. Sub-130 nm nanoparticles based on poly(D,L-lactide-co-glycolide) (PLGA) (50:50 PLGA and 75:25 PLGA) and poly(D,L-lactide) (PLA) have been examined in comparison with free p-THPP. For all formulations tested, uptake of photosensitizer into cells was dependent on concentration, time and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(51 citation statements)
references
References 29 publications
(40 reference statements)
2
49
0
Order By: Relevance
“…Examples of encapsulation of hydrophobic photosensitizers into nanomaterials are polymeric nanoparticles [88], e.g., a hydrophobic photosensitizer meso-tetra(phydroxyphenyl)porphyrin (m-THPP) encapsulated into polymeric nanoparticle poly(D,Llactide-co-glycolide) [89,90], dendrimer phthalocyanine (DPc)-encapsulated polymeric micelles (DPc/m) [32], polymeric protoporphyrin IX micelles [55], and organically modified silica-based nanoparticles [91] entrapping the photosensitizing anti-cancer drug 2-devinyl-2-(1-hexyloxyethyl) pyropheophorbide [59] have been used.…”
Section: Ps Linkermentioning
confidence: 99%
“…Examples of encapsulation of hydrophobic photosensitizers into nanomaterials are polymeric nanoparticles [88], e.g., a hydrophobic photosensitizer meso-tetra(phydroxyphenyl)porphyrin (m-THPP) encapsulated into polymeric nanoparticle poly(D,Llactide-co-glycolide) [89,90], dendrimer phthalocyanine (DPc)-encapsulated polymeric micelles (DPc/m) [32], polymeric protoporphyrin IX micelles [55], and organically modified silica-based nanoparticles [91] entrapping the photosensitizing anti-cancer drug 2-devinyl-2-(1-hexyloxyethyl) pyropheophorbide [59] have been used.…”
Section: Ps Linkermentioning
confidence: 99%
“…Simillar conclusions were observed by Konan et al (2003) with sub-130 nm nanoparticles of PLGA loaded with Meso-tetra(4-hydroxyphenyl)porphyrin (p-THPP) with incubating time of 15 or 30 min on EMT-6 mammary tumor cells evaluated subcellular localization and efflux of EMT-6 tumor mammary cells in comparison with the free dye. These results suggest that for each cell line the incubation time is an important parameter to be investigated to obtain the best results in PDT.…”
Section: Ultrastructural Analysismentioning
confidence: 97%
“…130,131,193195 Once the particles are internalized, intracellular trafficking is dependent on the physicochemical properties of the particles, such as surface charge, polymer coat, and surface modifications. 85 Konan and coworkers observed that meso-tetra-(4-hydroxyphenyl)porphyrin ( p -THPP)-PLGA nanoparticles were accumulated intracellularly 1.3-fold better than p -THPP-poly (D,L-lactide) (PLA) nanoparticles, 196 suggesting that the presence of glycolic acid, imparting a hydrophilic character to the nanoparticle, enhanced cellular sequestration. Cerium nanoparticles were taken up by a clathrin-dependent mechanism and trafficked throughout the cell, supporting the use of these nanoparticles as intracellular scavengers of reactive oxygen and reactive nitrogen species.…”
Section: Potential Of Nanotherapeuticsmentioning
confidence: 99%